2003
DOI: 10.1038/sj.bjc.6601234
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of minichromosome maintenance protein-2 and Ki67 in laryngeal squamous epithelial lesions

Abstract: Histological classification of laryngeal epithelial lesions is highly subjective, and methods of cytological detection are not well developed. Improved determination of aberrant cell cycle entry may allow increased objectivity in histological assessment and enable the development of less invasive diagnostic cytology tests. Sections of normal larynx (n ¼ 10), laryngeal dysplasia (n ¼ 20) and laryngeal squamous cell carcinoma (SCC) (n ¼ 10) were classified according to the Ljubljana classification and stained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
70
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 23 publications
(28 reference statements)
14
70
0
5
Order By: Relevance
“…In the normal larynx, Mcm-2 expression was confined to the basal layers of the epithelium, with the surface epithelium failing to show any Mcm-2 expression, as described previously (Chatrath et (Chatrath et al, 2003). In keeping with our findings at other anatomical sites (Freeman et al, 1999), the highest LI values were observed in the less well differentiated SCCs.…”
Section: Expression Of Mcm-2 and Ki67supporting
confidence: 90%
See 2 more Smart Citations
“…In the normal larynx, Mcm-2 expression was confined to the basal layers of the epithelium, with the surface epithelium failing to show any Mcm-2 expression, as described previously (Chatrath et (Chatrath et al, 2003). In keeping with our findings at other anatomical sites (Freeman et al, 1999), the highest LI values were observed in the less well differentiated SCCs.…”
Section: Expression Of Mcm-2 and Ki67supporting
confidence: 90%
“…Features predictive of tumour aggression and poor ultimate survival are not consistently demonstrated on histopathological evaluation (Gale et al, 2000), giving rise to an inevitable degree of subjectivity and variability in diagnosis (Hellquist et al, 1999). Given the potentially mutilating and functionally disabling nature of aggressive laryngeal surgical interventions, a drive towards earlier detection and more reliable stratification of laryngeal dysplastic and malignant lesions would be welcome and indeed is essential if further attempts to improve quality of life and outcome are to be realised (Chatrath et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in pre-malignant cervical intraepithelial neoplasia (CIN), the cellular proliferative compartment expands in proportion to histological grade, resulting in MCM-positive cells being present at the epithelial surface. We demonstrated that such aberrant expression can be exploited to improve detection of abnormal cells in cervical smears (Williams et al, 1998) and subsequently showed that the principle can be extended to early detection of neoplasia at other sites, including large bowel (Davies et al, 2002), larynx (Chatrath et al, 2003) and oral cavity (Scott et al, 2006).…”
mentioning
confidence: 99%
“…Most of these studies focused on the detection of MCM2 (Freeman et al, 1999;Chatrath et al, 2003;Davidson et al, 2003;Kodani et al, 2003;Scott et al, 2004). So far only few investigations studied MCM6 expression (Labib et al, 2001;Helfenstein et al, 2004).…”
mentioning
confidence: 99%